Presentation of Branchial Cleft Anomalies: Case Reports and Review of Literature - Pokharel, Apar; Rao, TS; Pandey, Bikash; Bhandary, Chhanya; Bhatt, Prashant; Jaiswal, Suvechhya (Journal of College of Medical Sciences-Nepal, 2018)
Type 2 branchial cleft anomalies are the most common cause of lateral neck swelling. We report two cases of type 2 branchial cleft anomalies. The first case is branchial cleft cyst and the second one is branchial fistula. Both cases were managed surgically. The post operative outcomes were uneventful. Second branchial cleft anomalies are the most common branchial anomalies. Branchial cysts are more common than sinuses and branchial fistulae are extremely rare. There is no gender predilection. The location, clinical symptoms and imaging findings aid in the diagnosis of this condition. Surgical excision is the mainstay of treatment. Keywords: branchial cleft; branchial cyst; branchial fistula.